A high polymer nano film and a preparation method thereof

CN118809903BActive Publication Date: 2026-11-03TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410877571.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2026-11-03
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

Existing technologies make it difficult to prepare highly crystalline conductive polymer films, especially for poorly soluble conductive polymers such as polyaniline and polypyrrole. Furthermore, stabilizers such as sodium polystyrene sulfonate are difficult to remove, which affects the crystallinity and electrical properties of the film.

Method used

Highly crystalline conductive polymer nanofilms were prepared by using dielectric-assisted pulsed laser evaporation combined with freezing and annealing, selecting appropriate solvents and solvent characteristic absorption wavelengths, removing stabilizers, and restoring conductivity through acid treatment.

Benefits of technology

A highly crystalline conductive polymer nanofilm without stabilizers was prepared, which improved the film's moisture resistance and electrical properties, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118809903B_ABST
    Figure CN118809903B_ABST
Patent Text Reader

Abstract

The application provides a kind of polymer nanometer film and its preparation method, belongs to the field of polymer film material.Preparation method is: conductive polymer material is dissolved in solvent, then is frozen into sample tank, again sample tank is placed in vacuum chamber, the substrate in front of sample tank is preheated, then the solution frozen in sample tank is deposited using medium assisted pulsed laser evaporation technology, to obtain original film, finally the original film is annealed, acid treated and dried to obtain polymer nanometer film.The crystallinity of polymer nanometer film is 60% to 90%, the thickness is 50nm to 450nm, and the conductivity is 0.01S / cm to 100S / cm.Compared with the film prepared by solution method, the polymer nanometer film of the application does not contain stabilizer component, has high crystallinity, excellent electrical properties and is easy to scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer thin film materials, specifically relating to a polymer nanofilm and its preparation method. Background Technology

[0002] Compared to traditional metallic and inorganic semiconductor materials, which suffer from drawbacks such as high density, high cost, and susceptibility to corrosion, conductive polymer materials offer advantages such as light weight, good flexibility, corrosion resistance, simple processing, and low cost. They hold promise as alternatives to metals and traditional inorganic semiconductor materials, reducing industrial production costs, improving product quality and performance, and meeting diverse application needs. Conductive polymer thin films are a crucial component of organic electronic devices, and their quality directly determines the performance of these devices. However, the high molecular weight of polymers makes it difficult to guarantee molecular order and orientation during film formation, ultimately affecting the crystallinity and electrical properties of the film and hindering the development of high-performance organic electronic devices. Therefore, the preparation of highly crystalline conductive polymer thin films is of great significance.

[0003] Currently, solution-based methods are widely used to prepare polymer thin films, including simple coating, dip-coating, spin-coating, and blade coating. These methods primarily involve preparing a polymer solution, uniformly coating it onto a substrate using different methods, and then forming a thin film through solvent evaporation or heat treatment. Techniques such as spin-coating and blade coating are relatively mature, simple to operate, and produce relatively uniform film thicknesses, making them the mainstream methods for preparing polymer thin films. However, these methods also have many drawbacks, such as the need for strong affinity between the substrate and the polymer solution; otherwise, the prepared film quality is poor and prone to detachment; the prepared film thickness is relatively large, making it difficult to control at the nanoscale; and the solvent from secondary deposition can damage the previously deposited film, hindering multilayer material deposition.

[0004] More importantly, traditional conductive polymers such as polyaniline and polypyrrole are generally difficult to dissolve in common volatile solvents, significantly limiting the application of solution-based film formation methods (such as spin coating). Therefore, current techniques typically involve adding solubilizing stabilizers, such as sodium polystyrene sulfonate, to the poorly soluble conductive polymers to promote dissolution before preparing films via solution processing. However, the interaction between stabilizers and conductive polymers is strong, making it difficult to remove the stabilizer components during solution-based film formation. This results in conductive polymer films prepared using existing techniques containing a large amount of stabilizer. On the one hand, the presence of stabilizers hinders the orderly stacking of conductive polymer molecular chains, affecting the crystallinity of the conductive polymer film and reducing its quality. On the other hand, polymer films containing stabilizers are prone to deliquescence in air, rendering them unusable. Therefore, it is essential to improve the preparation process of conductive polymer films to remove added stabilizer components, thereby improving film stability, crystallinity, and overall film quality. Summary of the Invention

[0005] This invention is made to solve the above-mentioned problems, and its purpose is to provide a polymer nanofilm and a method for preparing the same.

[0006] This invention provides a method for preparing polymer nanofilms, characterized by the following steps: S10, after preparing a conductive polymer material, dissolving the conductive polymer material in a solvent to obtain a first solution, wherein the conductive polymer material includes polyaniline and / or polypyrrole, and the prepared conductive polymer material contains sodium polystyrene sulfonate as a stabilizer for solubilization; S20, immersing the first solution in a sample cell and cooling it to freeze, then placing the sample cell in a vacuum chamber, wherein the cooling temperature is adjusted according to the concentration of the first solution; S30, after preheating the substrate in front of the sample cell placed in the vacuum chamber, using a dielectric-assisted pulsed laser evaporation device to evaporate the frozen first solution in the sample cell. Deposition yields the original thin film. The substrate preheating temperature is selected based on the differential scanning calorimetry results of the conductive polymer material. The laser wavelength of the dielectric-assisted pulsed laser evaporation equipment is matched with the characteristic absorption wavelength of the solvent. In step S40, the original thin film undergoes annealing and acid treatment, followed by drying to obtain a polymer nanofilm. The annealing temperature is selected based on the differential scanning calorimetry results of the conductive polymer material. The polymer nanofilm has a crystallinity of 60%–90%, a thickness of 50 nm–450 nm, and an electrical conductivity of 0.01 S / cm–100 S / cm. The polymer nanofilm does not contain sodium polystyrene sulfonate and exhibits good moisture resistance.

[0007] The method for preparing polymer nanofilms provided by the present invention may also have the following feature: in step S10, the solvent includes any one or more of methanol, ethanol, dimethyl sulfoxide or N,N-dimethylformamide.

[0008] The method for preparing polymer nanofilms provided by the present invention may also have the following feature: in step S10, the concentration of the conductive polymer material in the first solution is 0.05wt% to 3wt%.

[0009] The method for preparing polymer nanofilms provided by the present invention may also have the following feature: in step S20, the cooling method is to use liquid nitrogen to cool to between -80°C and -170°C.

[0010] The method for preparing polymer nanofilms provided by this invention may also have the following features: In step S20, the concentration of the conductive polymer material in the first solution is denoted as ω, and the cooling temperature is denoted as T. When ω = 0.05 wt%, T ∈ [-135, -90] ℃; when ω = 0.1 wt%, T ∈ [-140, -110] ℃; when ω = 0.5 wt%, T ∈ [-150, -130] ℃; when ω = 1 wt%, T ∈ [-155, -135] ℃; when ω = 2 wt%, T ∈ [-160, -140] ℃; and when ω = 3 wt%, T ∈ [-170, -160] ℃.

[0011] The method for preparing polymer nanofilms provided by the present invention may also have the following features: in step S30, the substrate preheating temperature is 40℃~160℃ and the deposition time is 1min~50min.

[0012] The method for preparing polymer nanofilms provided by the present invention may also have the following features: in step S30, when the conductive polymer material is polyaniline, the substrate preheating temperature is 50℃~160℃, and when the conductive polymer material is polypyrrole, the substrate preheating temperature is 40℃~130℃.

[0013] The method for preparing polymer nanofilms provided by the present invention may also have the following features: in step S40, the annealing treatment is performed by annealing at 100℃-160℃ for 1h to 24h in a tube furnace under a nitrogen atmosphere, and the acid treatment is performed by immersing in a sulfuric acid solution with a concentration of 0.2mol / L to 4mol / L (calculated as hydrogen ions) for 1h to 24h.

[0014] The method for preparing polymer nanofilms provided by the present invention may also have the following features: in step S40, when the conductive polymer material is polyaniline, the annealing temperature is 100℃~160℃, and when the conductive polymer material is polypyrrole, the annealing temperature is 100℃~130℃.

[0015] The present invention also provides a polymer nanofilm, characterized in that it is prepared by any of the preceding polymer nanofilm preparation methods.

[0016] The advantages of this invention compared to the prior art are as follows:

[0017] (1) For the poorly soluble conductive polymers polyaniline and polypyrrole, sodium polystyrene sulfonate was introduced as a stabilizer to promote their dissolution. Then, by improving the polymer film preparation technology, a highly crystalline conductive polymer nanofilm was prepared using medium-assisted pulsed laser evaporation technology. At the same time, the stabilizer component was removed to improve the moisture resistance of the polymer film.

[0018] (2) Compared with thin films prepared by solution method, the conductive polymer nanofilm obtained by the present invention does not contain stabilizer components, has high crystallinity, excellent electrical properties, and the preparation method is easy to scale up. Attached Figure Description

[0019] Figure 1 This is a flowchart of the preparation method of polymer nanofilm in Example 1 of the present invention;

[0020] Figure 2 This is a differential scanning calorimetry result graph of polyaniline in Example 1 of the present invention;

[0021] Figure 3 This is a scanning electron microscope cross-sectional view of the polymer nanofilm in Example 1 of the present invention;

[0022] Figure 4 This is the grazing incidence X-ray diffraction pattern of the polymer nanofilm in Example 1 of the present invention;

[0023] Figure 5 This is the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm of Example 1 of the present invention;

[0024] Figure 6 This is a differential scanning calorimetry result diagram of polypyrrole in Example 2 of the present invention;

[0025] Figure 7 This is a scanning electron microscope cross-sectional view of the polymer nanofilm in Example 2 of the present invention;

[0026] Figure 8 This is the grazing incidence X-ray diffraction pattern of the polymer nanofilm in Example 2 of the present invention;

[0027] Figure 9 This is the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm of Example 2 of the present invention;

[0028] Figure 10 This is a scanning electron microscope cross-sectional view of the polymer film prepared in the comparative example of the present invention;

[0029] Figure 11 This is the grazing incidence X-ray diffraction pattern of the polymer film in the comparative example of the present invention; Figure 12 This is the XPS spectrum of the 2p orbital of sulfur in the polymer film of the comparative example of the present invention. Detailed Implementation

[0030] To make the technical means, creative features, objectives and effects of the present invention easy to understand, the following embodiments, in conjunction with the accompanying drawings, specifically illustrate a polymer nanofilm and its preparation method.

[0031] <Example 1>

[0032] Figure 1 This is a flowchart illustrating the preparation method of the polymer nanofilm in Example 1 of the present invention. Figure 1 As shown, this embodiment provides a method for preparing polymer nanofilms, including the following steps:

[0033] S10, the conductive polymer material is ultrasonically stirred at 2wt% to dissolve in a solvent (methanol in this example) to obtain a first solution.

[0034] The conductive polymer material is polyaniline, and its preparation method is as follows:

[0035] S01, 0.01 mol stabilizer (sodium polystyrene sulfonate), 0.05 mol sulfuric acid and 0.02 mol aniline were dissolved in 20 mL of deionized water and mechanically stirred for 1 h to obtain the first reaction solution;

[0036] SO2, dissolve 0.02 mol ammonium persulfate in 10 mL of deionized water to obtain the second reaction solution;

[0037] S03, after mixing the first reaction solution and the second reaction solution, ultrasonically stir in an ice-water bath for 2 hours;

[0038] S04, add an equal volume of acetone to the mixture in step S03, separate the precipitate and dry it to obtain polyaniline (containing sodium polystyrene sulfonate).

[0039] S20, take 5 mL of the first solution and put it into the circular sample cell of the stainless steel target, freeze it to -140°C with liquid nitrogen, and then place the sample cell in the vacuum chamber.

[0040] S30, the substrate placed in front of the sample cell in the vacuum chamber is preheated to 50°C, and the first solution frozen in the sample cell is deposited for 10 minutes using a medium-assisted pulsed laser evaporation device to obtain the original thin film.

[0041] In this step, the solvent of the first solution is methanol, which has a characteristic absorption wavelength of 1064 nm (i.e., the solvent methanol undergoes OH stretching vibration at a wavelength of 1064 nm). The laser wavelength emitted by the medium-assisted pulsed laser evaporation device is the same as the characteristic absorption wavelength of the solvent methanol, which is 1064 nm.

[0042] S40: Place the original film in a tube furnace and anneal it at 150°C for 12 hours in a nitrogen atmosphere; after annealing, soak the original film in a 1 mol / L sulfuric acid solution for 3 hours, and then dry it in a 70°C oven for 6 hours to obtain a polymer nanofilm.

[0043] Figure 2 This is a differential scanning calorimetry (DSC) result graph of polyaniline in Example 1 of the present invention. Figure 2 As shown, in this embodiment, the substrate preheating temperature in step S30 and the annealing temperature in step S40 are selected based on the differential scanning calorimetry results of polyaniline.

[0044] Figure 3 This is a scanning electron microscope cross-sectional image of the polymer nanofilm in Example 1 of the present invention. Figure 2 As shown, this embodiment also provides a polymer nanofilm, which is prepared by the polymer nanofilm preparation method provided in this embodiment. Figure 3 As shown, the thickness of the polymer nanofilm in this embodiment is approximately 100 nm.

[0045] Figure 4 This is the grazing incidence X-ray diffraction pattern of the polymer nanofilm in Example 1 of the present invention.

[0046] Crystallinity = A c / (A c +A a )×100% (Formula 1)

[0047] Among them, A c For the area of ​​the crystallization peak, A a The area represents the amorphous peak. In this embodiment, the crystalline peaks are sharp peaks with diffraction angles 2θ of 16.2°, 17.4°, 19.2°, 23.0°, and 25.5°, while the amorphous peaks are broad peaks with diffraction angles 2θ in the range of 15° to 25°. The corresponding areas can be obtained by peak segmentation.

[0048] according to Figure 4 As can be seen from the formula for calculating crystallinity above, the crystallinity of the polymer nanofilm in this embodiment is 89.3%.

[0049] Figure 5 This is the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm of Example 1 of the present invention. Figure 5As shown, the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm in this embodiment contains only a pair of peaks at 169.41 eV and 168.25 eV, corresponding to sulfur in the doped acid sulfuric acid, but does not contain sulfur components in the stabilizer polystyrene sulfonate (whose corresponding peaks are generally located at about 170.0 eV and 168.8 eV), indicating that the film does not contain stabilizers.

[0050] This embodiment enables the preparation of polymer films without the stabilizer sodium polystyrene sulfonate by matching the wavelength of the pulsed laser with the characteristic absorption wavelength of the solvent. In this embodiment, the wavelength of the pulsed laser is selected as 1064 nm, and the solvent methanol undergoes OH stretching vibration at a wavelength of 1064 nm. Through laser energy resonance, the solvent can absorb a large amount of energy, converting the target material into low-temperature plasma. In the prior art, sodium polystyrene sulfonate is difficult to remove from conductive polymer films, mainly because it carries a negative charge and has a strong electrostatic interaction with the positively charged polyaniline. In this embodiment, by forming a low-temperature plasma, the strong collisions between particles can achieve dedoping (i.e., neutralization) of polyaniline, thereby disrupting the electrostatic interaction between sodium polystyrene sulfonate and polyaniline, allowing sodium polystyrene sulfonate to leave the system and not be deposited into the polymer film. Because polyaniline undergoes dedoping in step S30 and loses its conductivity, it must be acid-treated (i.e., doped) in step S40 to restore its conductivity.

[0051] The conductivity of the polymer nanofilm in this embodiment was found to be 1.71 S / cm using a Keithley 2400 source meter with a four-probe method.

[0052] <Example 2>

[0053] This embodiment provides a method for preparing polymer nanofilms, including the following steps:

[0054] S10, the conductive polymer material is ultrasonically stirred at 2wt% to dissolve in a solvent (methanol in this example) to obtain a first solution.

[0055] The conductive polymer material is polypyrrole, and its preparation method is as follows:

[0056] S01, 0.0025 mol of stabilizer (sodium polystyrene sulfonate), 0.03 mol of sulfuric acid and 0.03 mol of pyrrole were dissolved in 30 mL of deionized water and mechanically stirred for 1 h to obtain the first reaction solution;

[0057] SO2, dissolve 0.03 mol ammonium persulfate in 20 mL of deionized water to obtain the second reaction solution;

[0058] S03, after mixing the first reaction solution and the second reaction solution, ultrasonically stir in an ice-water bath for 3 hours;

[0059] S04, add an equal volume of acetone to the mixture in step S03, separate the precipitate and dry it to obtain polypyrrole (containing sodium polystyrene sulfonate).

[0060] S20, take 5 mL of the first solution and put it into the circular sample cell of the stainless steel target, freeze it to -150°C with liquid nitrogen, and then place the sample cell in the vacuum chamber.

[0061] S30, the substrate placed in front of the sample cell in the vacuum chamber is preheated to 40°C, and the first solution frozen in the sample cell is deposited for 30 minutes using a medium-assisted pulsed laser evaporation device to obtain the original thin film.

[0062] In this step, the solvent of the first solution is methanol, which has a characteristic absorption wavelength of 1064 nm (i.e., the solvent methanol undergoes OH stretching vibration at a wavelength of 1064 nm). The laser wavelength emitted by the medium-assisted pulsed laser evaporation device is the same as the characteristic absorption wavelength of the solvent methanol, which is 1064 nm.

[0063] S40: Place the original film in a tube furnace and anneal it at 120°C for 12 hours in a nitrogen atmosphere. After annealing, soak the original film in a 1 mol / L sulfuric acid solution for 3 hours, and then dry it in a 70°C oven for 6 hours to obtain a polymer nanofilm.

[0064] Figure 6 This is a differential scanning calorimetry (DSC) result graph of polypyrrole in Example 2 of the present invention. (See figure) Figure 6 As shown, in this embodiment, the substrate preheating temperature in step S30 and the annealing temperature in step S40 are selected based on the differential scanning calorimetry results of polypyrrole.

[0065] Figure 7 This is a scanning electron microscope cross-sectional image of the polymer nanofilm in Example 2 of the present invention. Figure 7 As shown, this embodiment also provides a polymer nanofilm, which is prepared by the polymer nanofilm preparation method provided in this embodiment. Figure 7 As shown, the thickness of the polymer nanofilm in this embodiment is approximately 150 nm.

[0066] Figure 8 This is the grazing incidence X-ray diffraction pattern of the polymer nanofilm in Example 2 of the present invention.

[0067] In this embodiment, the crystalline peaks are sharp peaks with diffraction angles 2θ of 16.3°, 17.5°, 19.2°, 23.1° and 25.6°, and the amorphous peaks are broad peaks with diffraction angles 2θ in the range of 15° to 25°. The corresponding areas can be obtained by peak division.

[0068] according to Figure 8 As can be seen from the formula (Equation 1) for calculating crystallinity in Example 1, the crystallinity of the polymer nanofilm in this example is 84.1%.

[0069] Figure 9 This is the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm of Example 2 of the present invention. Figure 9 As shown, the XPS spectrum of the 2p orbital of sulfur in the polymer nanofilm of this embodiment contains only a pair of peaks at 169.57 eV and 168.23 eV, corresponding to sulfur in the dopant acid sulfuric acid, and does not contain the sulfur component of the stabilizer polystyrene sulfonate (whose corresponding peaks are generally located at approximately 170.0 eV and 168.8 eV), indicating that the film does not contain a stabilizer. The reason why this embodiment can prepare a polymer film without the stabilizer sodium polystyrene sulfonate is the same as in Example 1, and will not be repeated.

[0070] The conductivity of the polymer nanofilm in this embodiment was found to be 0.43 S / cm using a Keithley 2400 source meter with a four-probe method.

[0071] <Comparative Example>

[0072] This comparative example shows the preparation of polymer films according to existing polymer film preparation methods, followed by performance testing.

[0073] The preparation method of the polymer film in this comparative example is as follows:

[0074] S10, the conductive polymer material is ultrasonically stirred at 2wt% to dissolve in the solvent methanol to obtain the first solution.

[0075] The conductive polymer material is polyaniline, and its preparation method is the same as in Example 1.

[0076] S20 uses a desktop spin coater (KW-4A type, Institute of Microelectronics, Chinese Academy of Sciences) to prepare polymer films via spin coating.

[0077] The homogenization time was 30 seconds and the rotation speed was 10,000 rpm.

[0078] S30: The film is placed in a tube furnace and annealed at 150°C for 12 hours in a nitrogen atmosphere. Because the film is prone to deliquescence, acid treatment is not possible.

[0079] Figure 10 This is a scanning electron microscope cross-sectional image of the polymer thin film prepared in the comparative example of this invention. For example... Figure 10 As shown, the thickness of the polymer film in the comparative example is approximately 2 μm. This indicates that the thickness of polymer films prepared by existing techniques is not within the nanoscale.

[0080] Figure 11 This is a grazing incidence X-ray diffraction pattern of the polymer thin film in the comparative example of the present invention.

[0081] In this comparative example, the crystalline peaks are sharp peaks with diffraction angles 2θ of 16.3°, 17.4°, 19.2°, 23.0° and 25.5°, while the amorphous peaks are broad peaks with diffraction angles 2θ in the range of 15° to 25°. The corresponding areas can be obtained by peak division.

[0082] according to Figure 11 As can be seen from the formula (Equation 1) used to calculate the crystallinity in Example 1, the crystallinity of the polymer film in this comparative example is 55.6%. This indicates that the crystallinity of the polymer film prepared by the prior art is much lower than that of the polymer nanofilms provided in Examples 1 and 2.

[0083] Figure 12 This is the XPS spectrum of the 2p orbital of sulfur in the polymer film of the comparative example of this invention. Figure 12 As shown, the XPS spectrum of the 2p orbital of sulfur in the polymer film of this comparative example contains a pair of peaks at 169.41 eV and 168.32 eV, corresponding to sulfur in the doped acid sulfuric acid, and a pair of peaks at 169.98 eV and 168.74 eV, corresponding to sulfur in the stabilizer polystyrene sulfonate, indicating that the stabilizer cannot be removed from the polymer film prepared by the prior art.

[0084] The conductivity of the polymer nanofilm in this comparison was measured to be 0.65 S / cm using a Keithley 2400 source meter with a four-probe method. This indicates that the conductivity of the polymer film prepared by the prior art is lower than that of the polymer nanofilm provided in Example 1.

[0085] Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a polymer nanofilm, characterized in that, Includes the following steps: S10, after preparing the conductive polymer material, dissolve the conductive polymer material in a solvent to obtain a first solution. The conductive polymer material includes polyaniline and / or polypyrrole, and the prepared conductive polymer material contains sodium polystyrene sulfonate as a stabilizer for solubilization. S20, the first solution is placed into the sample cell and cooled to freeze, and then the sample cell is placed in a vacuum chamber. The cooling temperature is adjusted according to the concentration of the first solution; S30: After preheating the substrate placed in front of the sample tank within the vacuum chamber, the first solution frozen in the sample tank is deposited using a dielectric-assisted pulsed laser evaporation device to obtain the original thin film. The substrate preheating temperature is selected based on the differential scanning calorimetry results of the conductive polymer material, and the laser wavelength of the medium-assisted pulsed laser evaporation device is matched with the characteristic absorption wavelength of the solvent. S40, the original film is subjected to annealing and acid treatment successively, followed by drying to obtain the polymer nanofilm. The annealing temperature is selected based on the differential scanning calorimetry results of the conductive polymer material. The polymer nanofilm has a crystallinity of 60%~90%, a thickness of 50 nm~450 nm, and an electrical conductivity of 0.01 S / cm~100 S / cm. The polymer nanofilm does not contain sodium polystyrene sulfonate.

2. The method for preparing polymer nanofilms according to claim 1, characterized in that: in, In step S10, the solvent includes any one or more of methanol, ethanol, dimethyl sulfoxide, or N,N-dimethylformamide.

3. The method for preparing polymer nanofilms according to claim 1, characterized in that: in, In step S10, the concentration of the conductive polymer material in the first solution is 0.05 wt% to 3 wt%.

4. The method for preparing polymer nanofilms according to claim 1, characterized in that: in, In step S20, the cooling method is to use liquid nitrogen to cool the temperature to between -80 ℃ and -170 ℃.

5. The method for preparing polymer nanofilms according to claim 4, characterized in that: in, In step S20, the concentration of the conductive polymer material in the first solution is denoted as ω, and the cooling temperature is denoted as T. When ω = 0.05 wt%, T ∈ [-135, -90]℃. When ω = 0.1 wt%, T ∈ [-140, -110]℃. When ω = 0.5 wt%, T ∈ [-150, -130]℃. When ω = 1 wt%, T ∈ [-155, -135]℃. When ω = 2 wt%, T ∈ [-160, -140]℃. When ω=3 wt%, T∈[-170, -160]℃.

6. The method for preparing polymer nanofilms according to claim 1, characterized in that: in, In step S30, the substrate preheating temperature is 40 ℃~160 ℃. The deposition time is 1 min to 50 min.

7. The method for preparing polymer nanofilms according to claim 1 or 6, characterized in that: in, In step S30, when the conductive polymer material is polyaniline, the substrate preheating temperature is 50 ℃~160 ℃. When the conductive polymer material is polypyrrole, the substrate preheating temperature is 40 ℃~130 ℃.

8. The method for preparing polymer nanofilms according to claim 1, characterized in that: in, In step S40, the annealing process is as follows: annealing in a tube furnace under a nitrogen atmosphere at 100℃-160℃ for 1 h to 24 h. The acid treatment method is as follows: soaking in a sulfuric acid solution with a hydrogen ion concentration of 0.2 mol / L to 4 mol / L for 1 h to 24 h.

9. The method for preparing polymer nanofilms according to claim 1 or 8, characterized in that: in, In step S40, when the conductive polymer material is polyaniline, the annealing temperature is 100 ℃~160 ℃. When the conductive polymer material is polypyrrole, the annealing temperature is 100 ℃~130 ℃.

10. A polymer nanofilm, characterized in that, It is prepared by the method for preparing polymer nanofilms according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite conductive film, preparation method thereof and thin film transistor

    CN112635102A

  • Method of forming conductive polymeric nanocomposite materials and materials produced thereby

    US20030039816A1